To what extent does human capital diversity moderate the relationship between HRM practices and organizational performance: Evidence from Spanish firms - Triguero-Sánchez,Rafael (2016)
The purpose of this research study is to explore the moderating effect the diversity of human capital may have on the relationship between HRM practices and business performance. To this end, factors determining of human capital diversity have been used. With a sample of more than one hundred Spanish companies we have carried out a factor analysis-principal axis factoring with varimax rotation- on identified HRM practices and perceived organizational performance as factors with good factor loadings, and consistent with the proposed model. Our findings indicate that the human capital factors such as education level," functional specialization and length of service condition the effects of HRM-practices on organizational performance. The literature pays little attention to non-linear models. Examining the factors' determining human capital diversity casts some light on the black box of the relationship between human resources practices and organizational performance.